Physico-mechanical properties of black pepper (Piper nigrum L.) - T J Zachariah, Vikram Vikram, S Balasubramanian, R Kumar, K K Singh (Journal of Spices and Aromatic Crops, 2013)
The physical and mechanical properties of black pepper were determined as a function of moisture content in the range of 3.3% to 18.1% (d.b.). The average axial dimensions, major, medium and minor increased linearly from 4.92 mm to 5.37 mm, 4.59 mm to 5.08 mm and 4.42 mm to 4.89 mm, respectively. The geometric mean diameter, sphericity, unit volume, surface area and thousand seed weight increased from 4.63 mm to 5.10 mm, 0.94 mm3 to 0.95 mm3, 53.06 mm3 to 70.35 mm3, 67.65 mm2 to 81.87 mm2 and 42.82 g to 56.04 g, respectively with increase in moisture content from 3.3% to 18.1%. The true density increased linearly from 987.7 to 1012.2 kgm-3, while the bulk density decreased linearly from 556.8 to 542.7 kgm-3 and the porosity increased linearly with increase in moisture content. The angle of repose increased linearly from 22.30° to 33.66° and the coefficient of friction increased linearly from 0.705 to 0.936 with increase in moisture content. The coefficient of friction was found to be maximum against plywood. The force and energy absorbed at rupture point decreased non-linearly from 74.6 N to 50.1 N and 42.9 kJ to 32.8 kJ while the deformation increased non-linearly from 0.575 mm to 0.650 mm with increase in moisture content.